R & D Reactions to High-Technology Import Competition - Scherer, F. M.; Huh, Keun (The Review of Economics and Statistics, 1992)
For a seventeen-year panel covering 308 U.S. manufacturing corporations, we analyze firms' R&D spending reactions to changes in high-technology imports. On average, companies reduced their R&D/sales ratios in the short run as imports rose. Individual company reactions were heterogeneous, especially for multinational firms. Short-run reactions were more aggressive (i.e., tending toward R&D/sales ratio increases), the more concentrated the markets were in which the companies operated, the larger the company was, and the more diversified the firm's sales mix was. Reactions were less aggressive when special trade barriers had been erected or patent protection was strong in the impacted industries. Companies with a top executive officer educated in science or engineering were more likely to increase R&D/sales ratios in response to an import shock, all else equal. Over the full 17-year sample period, reactions may have shifted toward greater average aggressiveness.